Formulation and Physical Quality Testing of Cleansing Balm from Centella Asiatica (L.) URB. Extract with Castor Oil (Ricinus Communis L.) as a Makeup Remover - Pramesty, Sevty Ardhia; Hasriyani, Hasriyani; Sukoharjanti, Bintari Tri (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: This study aimed to formulate and evaluate the physical quality of cleansing balm containing 3% Centella asiatica (L.). Urb. Extract with castor oil (Ricinus communis L.) at varying concentrations (30%, 35%, and 40%) to determine the optimal formulation as an effective and safe makeup remover. Research Method: An experimental laboratory design was conducted at the Cendekia Utama Kudus Institute of Health Technology. The Centella asiatica extract was obtained from UPT Lab Herbal Materia Medica Batu, East Java. Physical quality tests included organoleptic, homogeneity, pH, spreadability, adhesion, melting point, cleansing ability, and skin irritation tests. Data analysis was performed using SPSS, including tests for normality, homogeneity, One-Way ANOVA, and post hoc Tukey tests. Six female volunteers aged 18–30 participated in the irritation test. Results and Discussion: All formulations met physical quality standards. Formula 1 (3% Centella asiatica + 30% castor oil) demonstrated optimal results, exhibiting the best cleansing ability, easy rinsing, an ideal pH (5.61), good spreadability (4.91 cm), the highest adhesion (13.43 s), and no irritation in any of the volunteers and increasing the castor oil content above 35% reduced cleansing effectiveness, despite improving spreadability. No formulation caused erythema or edema during the 72-hour observation. Implications: The findings support the potential use of Centella asiatica and castor oil in natural, safe, and effective cleansing balm formulations. Future research should assess long-term stability, consumer acceptance, and potential scalability for commercial production.